Perampanel Add-on to Standard Radiochemotherapy in vivo Promotes Neuroprotection in a Rodent F98 Glioma Model - Lange, Falko; Hartung, Jens; Liebelt, Clara; Boisserée, Julius; Resch, Tobias; Porath, Katrin; Hörnschemeyer, Max Frederik; Reichart, Gesine; Sellmann, Tina; Neubert, Valentin; Kriesen, Stephan; Hildebrandt, Guido; et al. (Frontiers in Neuroscience, 2020)
An abnormal glutamate signaling of glioblastoma may contribute to both tumor progression and the generation of glioma-associated epileptic seizures. We hypothesized that the AMPA receptor antagonist perampanel could attenuate tumor growth and epileptic events. F98 glioma cells, grown orthotopically in Fischer rats, were employed as a model of glioma to investigate the therapeutic efficiency of perampanel (15 mg/kg) as adjuvant to standard radiochemotherapy. The epileptiform phenotype was investigated by video-EEG analysis and field potential recordings. Effects on glioma progression were estimated by tumor size quantification, survival analysis and immunohistological staining. Our data revealed that orthotopically-growing F98 glioma promote an epileptiform phenotype in rats. Radiochemotherapy reduced the tumor size and prolonged the survival of the animals. The adjuvant administration of perampanel had no effect on tumor progression. The tumor-associated epileptic events were abolished by perampanel application or radiochemotherapy respectively to initial baseline levels. Remarkably, perampanel preserved the glutamatergic network activity on healthy peritumoral tissue in RCT-treated animals. F98 tumors are not only a robust model to investigate glioma progression, but also a viable model to simulate a glioma-associated epileptiform phenotype. Furthermore, our data indicate that perampanel acts as a potent anticonvulsant and may protect the tumor-surrounding tissue as adjuvant to radiochemotherapy, but failed to attenuate tumor growth or promote animal survival.